UN NUEVO EUMYSOPINAE (RODENTIA, ECIDMYIDAE) DEL MIOCENO TARDÍO DE LA PROVINCIA DE LA PAMPA Y CONSIDERACIONES SOBRE LA HISTORIA DE LA SUBFAMILIA (Ameghiniana, 2014)
Pampamys emmonsae gen. el sp. nov., from the Cerro Azul Formation (Late Miocene, La Pampa province), is described. It is related to the extant Clyomys, Euryzygomatomys and Thrichomys . Dental morphology indicates that these genera represent a natural group, of which Pampamys emmonsae gen. et sp. nov. is the most primitive representative. This clade would have undergone an important radiation during the Late Miocene in central and western Argentina.